Implementation of Physical Education Learning in Short Service Badminton at SMA Negeri 3 Bengkulu Selatan - Yobi Rion Saputra (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the level of ability and implementation of short service physical education learning for extracurricular participants at SMA Negeri 3 Bengkulu Selatan. This research is a quantitative descriptive research. The method used is the observation method. The subjects of this study were students participating in extracurricular badminton at SMA Negeri 3 Bengkulu Selatan, totaling 15 students. The instrument used is a backhand short serve test. The data analysis technique used in this research is descriptive research with the percentage formula. The results of the study on the backhand short serve ability of badminton extracurricular participants of extracurricular members of SMA Negeri 3 Bengkulu Selatan were in the very good category (0%) with a score of >75. good category (0%) has a score of 66-75. the medium category (60%) has a score of 50-65. and students who fall into the less category as many as 8 students or (40%) have a score of 40-50.